Rapid and Simple Headspace Solid-Phase Microextraction for the Determination of Trace Organochlorine Pesticides in Sediment by Gas Chromatography - Wongklom, Amornrat (KKU Science Journal, 2013)
Rapid and simple headspace solid-phase microextraction (HS-SPME) technique with gas chromatography was developed for extraction and determination of 5-organochlorine pesticides (OPCs; heptachlor, aldrin, 4,4-DDE, 2,4-DDT, 4,4-DDT) in sediment. The parameters affecting the extraction process such as fiber type, extraction temperature and time, and the addition of hydrophilic solvents and salt were studied. For HS-SPME, the suspension of 0.5-g sediment in 1-mL of water was extracted in the headspace using 100-µm PDMS fiber with extraction temperature of 70 oC for 60 min, stirred during extraction. The OCPs was determined by GC-ECD with the optimum condition. The addition of hydrophilic solvents and sodium chloride had different effects on the extraction of OCPs. Higher responses of OCPs (4,4-DDE, 2,4-DDT, 4,4-DDT) were obtained when hydrophilic solvent was added to the sediment while heptachlor and aldrin slightly decreased and the response for adding the salt was the lowest. Sediment samples were collected from November 2010 to September 2011 from 6 stations starting from Amphoe Tatoom, Surin province to Amphoe Khongchiam, Ubon Ratchathani province (about 350 km). OCPs were found in all stations and quantities were in the range of 2.20 to 521 pg/g-dw of sediment. The quantities found were not over the values established by the Pollution Control Department for the soil quality.